Mindfulness-Based Stress Reduction Techniques in Educational Settings: A New Approach to Enhance Mental Health and Learning - Nur’aeni Nur’aeni; Him Patry (Yayasan Adra Karima Hubbi, 2024)
Background. Student mental health has become a significant concern in education, especially given the increasing academic and social pressures they face. Mindfulness-Based Stress Reduction (MBSR) techniques effectively reduce stress and improve mental well-being in various populations. However, their application in educational settings is still relatively new and requires further research to understand their impact. Purpose. This study aims to evaluate the effectiveness of MBSR techniques in improving students’ mental health and learning ability in educational environments. A key focus was to measure changes in stress levels, emotional well-being, and academic performance before and after the MBSR intervention. Method. This study used an experimental design with a control group. The study sample consisted of 100 high school students divided into two groups: an intervention group that received MBSR sessions for eight weeks and a control group that did not receive an intervention. Data were collected using stress scale questionnaires, emotional well-being scales, and academic performance records before and after the intervention. Data analysis was performed using descriptive statistical techniques and independent t-tests to compare results between the two groups. Results. The results showed that students who attended the MBSR program experienced a significant reduction in stress levels and improved emotional well-being compared to the control group. In addition, the student’s academic performance in the intervention group also showed better improvement than the control group, although this improvement was not statistically significant. Conclusion. This study concludes that MBSR techniques effectively reduce stress and improve students’ emotional well-being in educational settings. Although the improvement in academic performance was not statistically significant, these findings point to the potential of MBSR as a beneficial approach to improving students’ mental health and learning ability. Further research is recommended to explore the long-term impact of MBSR and the optimization of its application in educational contexts.